A Cross-Sectional Study to Assess Prevalence & Factors influencing Obesity, Overweight, and Underweight Among School Children in Mangalore - E, Karthikeyan; NJ, Priyadarisini; B R Alva, Avin (Journal of Neonatal Surgery, 2025)
Background: Childhood obesity is an emerging public health concern, coexisting with undernutrition in developing countries like India. This study aims to assess the prevalence and factors influencing obesity, overweight, and underweight among school children aged 10–15 years in Mangalore, with a comparative analysis of private and government schools. Methods: A cross-sectional study was conducted among 2,023 school children, selected randomly from government and private schools in urban and rural settings. Data on socioeconomic status, dietary habits, physical activity, and lifestyle factors were collected using structured questionnaires and anthropometric measurements. BMI was categorized using WHO BMI-for-age standards, and statistical analysis was performed using SPSS 16, with a Chi-square test and multivariate regression analysis applied to determine significant associations. Results: The overall prevalence of obesity, overweight, and underweight was 5.2%, 10.53%, and 24.72%, respectively. Obesity was significantly higher among private school children (7.88%) and urban residents (7.89%), whereas underweight was more prevalent among government school children (31.24%) and rural residents (30.92%) (p < 0.0001). Junk food consumption >2 times/week, sedentary screen time >2 hours/day, and lower physical activity were strongly associated with obesity (p < 0.0000001). Underweight was linked to lower socioeconomic status, inadequate calorie intake, and maternal unemployment (p < 0.0001). Conclusion: The study highlights the dual burden of malnutrition, with rising obesity and overweight in affluent urban children and persistent undernutrition among low-income groups. Dietary habits, sedentary behavior, physical activity, and socioeconomic factors play a crucial role in BMI variations. Targeted interventions focusing on balanced nutrition, increased physical activity, and lifestyle modifications are essential to address this growing public health issue.